Congestion-Aware Signaling Aggregation and Barring Scheme for LTE Based Machine-to-Machine Network - Fangmin Xu; Chao Qiu; Pengbiao Wang; Xiaokai Liu (International Journal of Distributed Sensor Networks)
With the recently progress of Machine-to-Machine (M2M) communication technology, especially the enormous M2M devices and unique service of M2M, some challenges are emerging to the traditional wireless access and core networks, especially the congestion problem due to simultaneously bursty M2M service. Following this paradigm, the purpose of this paper is to support and optimize the signaling aggregation and barring of M2M services based on cellular network. With LTE network being the example access network, a congestion-aware signaling aggregation and barring scheme is designed considering the various requirements of M2M services and the congestion situation in the network entity. Theoretical analysis and experimental simulations show that this scheme can improve the system efficiency and greatly alleviate the signaling congestion, especially for the bursty M2M service.